Realitas Implementasi Pengelolaan Keuangan Desa pada APBDes di Desa Dauh Peken - Purwa Astawa, I Wayan; Budiasih, I Gusti Ayu Nyoman (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 14 No 2 (2019), 2019)
One of the problems that appear in village financial management is the issue of its implementation in the Village Revenue and Expenditure Budget. The implementation is not in accordance with the provisions of Permendagri 113 of 2014 concerning village financial management due to the lack of common understanding, views, and commitments from village financial organizers. The purpose of this study was to determine the reality of the implementation of financial management of the village of Dauh Peken in Tabanan District, Tabanan Regency based on Permendagri 113 of 2014 on village financial management. The research is descriptive with a qualitative approach, research data obtained through in-depth interviews, observation, and documentation studies. This study was analyzed using the Case Study method. The results of the study indicate that the Dauh Peken Village has not fully complied with the provisions of the regulation in financial management during the implementation of the Village Revenue and Expenditure Budget. This requires synergy between the district and sub-district governments in terms of assistance and supervision of village finance providers.     Keywords: Village finance, regulations, village finance providers.